TPACK Capability Preservice Teachers Civic Education in the Era of Industrial Revolution 4.0 - Aulia Nursyifa; Imam Fitri Rahmadi; Eti Hayati (Jurnal Pendidikan Indonesia, 2020)
This research aims to determine the ability of the Technological Pedagogical Content Knowledge (TPACK) preservice teachers Civic education Pamulang University. The method used in this research is a quantitative method with a survey approach. The research subject amounted to 63 students. The results showed that the ability of TPACK has a very important role in improving the ability of preservice teachers in the revolution of the 4.0 industry, besides the analysis results demonstrated the ability of TPACK Preservice teachers Civic education on group A superior to the group B. Therefore, TPACK's capabilities need to be upgraded and supported by various parties to create an education that can produce future qualified teachers.